Non-Coding RNAs as Biomarkers and Therapeutic Targets for Diabetic Kidney Disease - Gu, Yue-Yu; Lu, Fu-Hua; Huang, Xiao-Ru; Zhang, Lei; Mao, Wei; Yu, Xue-Qing; Liu, Xu-Sheng; Lan, Hui-Yao (Frontiers in Pharmacology, 2021)
Diabetic kidney disease (DKD) is the most common diabetic complication and is a leading cause of end-stage kidney disease. Increasing evidence shows that DKD is regulated not only by many classical signaling pathways but also by epigenetic mechanisms involving chromatin histone modifications, DNA methylation, and non-coding RNA (ncRNAs). In this review, we focus on our current understanding of the role and mechanisms of ncRNAs, including microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the pathogenesis of DKD. Of them, the regulatory role of TGF-β/Smad3-dependent miRNAs and lncRNAs in DKD is highlighted. Importantly, miRNAs and lncRNAs as biomarkers and therapeutic targets for DKD are also described, and the perspective of ncRNAs as a novel therapeutic approach for combating diabetic nephropathy (DN) is also discussed.